Transinformação Vol. 26, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Transinformação Vol. 26, n. 1 (2014) Link de acesso ao númerohttp://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/issue/view/288